Japan fund for poverty reduction annual report 2016. (Asian Development Bank, 2018)
This publication presents the background and rationale, project implementation progress, and achievements of the Japan Fund for Poverty Reduction covering the period from 1 January to 31 December 2016.It contains general information about the fund project grants and technical assistance, with details about their operational performance during the year. Administered by the Asian Development Bank and established in May 2000, the fund provides direct grant assistance to the poorest and most vulnerable groups in Asia and the Pacific while fostering long-term social and economic development.